CITED2 mediates the mechanical loading–induced suppression of adipokines in the infrapatellar fat pad. Issue 1 (19th March 2019) - Liu, Lidi; He, Zhiyong; Xu, Lin; Lu, Laijin; Feng, Haotian; Leong, Daniel J.; Kim, Sun J.; Hirsh, David M.; Majeska, Robert J.; Goldring, Mary B.; Cobelli, Neil J.; Sun, Hui B.
Abstract: Adipokines secreted from the infrapatellar fat pad (IPFP), such as adipsin and adiponectin, have been implicated in osteoarthritis pathogenesis. CITED2, a mechanosensitive transcriptional regulator with chondroprotective activity, may modulate their expression. Cited2 haploinsufficient mice ( Cited2 +/− ) on a high‐fat diet (HFD) exhibited increased body weight and increased IPFP area compared to wild‐type (WT) mice on an HFD. While an exercise regimen of moderate treadmill running induced the expression of CITED2, as well as PGC‐1α, and reduced the expression of adipsin and adiponectin in the IPFP of WT mice on an HFD, Cited2 haploinsufficiency abolished the loading‐induced expression of PGC‐1α and loading‐induced suppression of adipsin and adiponectin. Furthermore, knocking down or knocking out CITED2 in adipose stem cells (ASCs)/preadipocytes derived from the IPFP in vitro led to the increased expression of adipsin and adiponectin and reduced PGC‐1α, and abolished the loading‐induced suppression of adipsin and adiponectin and loading‐induced expression of PGC‐1α. Overexpression of PGC‐1α in these ASC/preadipocytes reversed the effects caused by CITED2 deficiency. The current data suggest that CITED2 is a critical regulator in physiologic loading‐induced chondroprotection in the context of an HFD and PGC‐1α is required for the inhibitory effects of CITED2 on the expression of adipokines such as adipsin and adiponectin in the IPFP. Abstract : Adipokines secreted from the infrapatellar fat pad (IPFP) have been implicated in osteoarthritis. Exercise mitigates osteoarthritis and reduces IPFP volume in overweight adults. This article demonstrates a role for CITED2, a mechanosensitive transcriptional regulator with chondroprotective activity, in mediating the exercised‐induced suppression of adipokines in the IPFP, and also shows that PGC‐1α may be required for this inhibitory effect of CITED2.